2018
DOI: 10.1029/2017tc004830
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Topography of Eastern China Since the Latest Jurassic Period

Abstract: Some changes in the topography of eastern China since Late Jurassic times cannot be well explained by lithospheric deformation. Here we analyze global mantle flow models to investigate how mantle-driven long-wavelength topography may have contributed to shaping the surface topography of eastern China. Paleodrainage directions suggest that a southward tilted topography once existed in eastern north China in the latest Jurassic Period, which is different from that at present day (southeastward tilting). Our mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 67 publications
1
14
0
1
Order By: Relevance
“…The East China Floristic Province is one of the richest regions of plant diversity in the Sino-Japanese Floristic Region (Wu, 1979). The topography here is characterized by numerous plains and basins interspersed between low hills and median-high mountains (Cao et al, 2018). Those ranges, with a group of peaks exceeding 1,500 m in elevation, are scattered from the northeast (e.g., the Tianmu Mountains) to the southeast (e.g., the Wuyi Mountains), and from the northwest (e.g., the Dabie Mountains) to the southwest (e.g., the Luoxiao Mountains).…”
Section: Introductionmentioning
confidence: 99%
“…The East China Floristic Province is one of the richest regions of plant diversity in the Sino-Japanese Floristic Region (Wu, 1979). The topography here is characterized by numerous plains and basins interspersed between low hills and median-high mountains (Cao et al, 2018). Those ranges, with a group of peaks exceeding 1,500 m in elevation, are scattered from the northeast (e.g., the Tianmu Mountains) to the southeast (e.g., the Wuyi Mountains), and from the northwest (e.g., the Dabie Mountains) to the southwest (e.g., the Luoxiao Mountains).…”
Section: Introductionmentioning
confidence: 99%
“…Our research was carried out in the Chezhen depression, laying at the southeast of the Bohai Bay basin ( Figure 1b) [1]. It is one portion of a series of tectonic combinations of uplifts and depressions arranged in a northwest direction; it is adjacent to the Bohai bay and is bounded by the Tan-Lu strike-slip fault in the east and the Lan-Liao strikeslip fault in the west [41][42][43]. The Chezhen depression is a Cenozoic continental faulted basin developed based on the long-term reconstruction of the cratonic basement [1,3].…”
Section: Geological Informationmentioning
confidence: 99%
“…Some geochemical studies have suggested that the Mesozoic process could have been similar to the current subduction of the Pacific Plate beneath East Asia, forming a stagnant slab that extended down to the mantle transition zone Xu et al 2018). Recently, reconstructions of the time-dependent dynamic topography of Eastern China have indicated that the slab of the Palaeo-Pacific Plate subducted into the deeper section of the upper mantle beneath East Asia during the Early Cretaceous (Cao et al 2018). Meanwhile, the sinking and roll-back of the Palaeo-Pacific slab happened from the late Early Cretaceous to Late Cretaceous (Cao et al 2018).…”
Section: D Tectonic Implicationsmentioning
confidence: 99%
“…Recently, reconstructions of the time-dependent dynamic topography of Eastern China have indicated that the slab of the Palaeo-Pacific Plate subducted into the deeper section of the upper mantle beneath East Asia during the Early Cretaceous (Cao et al 2018). Meanwhile, the sinking and roll-back of the Palaeo-Pacific slab happened from the late Early Cretaceous to Late Cretaceous (Cao et al 2018). In addition, the lithospheric extensional setting of the eastern NCC during the late Mesozoic is suggested to be related to the possible slab roll-back of the Pacific Plate (Yang et al 2010;Li et al 2018c).…”
Section: D Tectonic Implicationsmentioning
confidence: 99%